Appendicular perforation - Malla, BR; Shrestha, RKM (Journal of Institute of Medicine Nepal, 2011)
Introduction: Appendicitis is the most common acute abdominal condition presenting in hospital. Appendicular perforation is a major complication of appendicitis. The objective of the study is review the cases of appendicular perforation in respect of its incidence, sex preference, clinicalfeatures, investigations, treatment and postoperative wound infectionsMethods: A retrospective study was conducted reviewing the records of the patients who were admitted in Dhulikhel hospital with the diagnosis of appendicular perforation from January 2009 to December 2010.Results: A total of 332 cases of appendicular disease were admitted during the study period. Out of them, 42 patients had appendicular perforation. It constituted 12.6% of total appendicular diseases. The male to female ratio in perforation was 6.1: 1. The common age group for the perforation was 30- 50 years with mean age of 35 years. The mean duration of pain before presentation to the hospital was 4.5 days.All the cases of appendicular perforation had spread of pain from right iliac fossa to all over the abdomen, and anorexia. Vomiting was found in 83.33% of the cases. All the cases had rebound tenderness and rigidity all over the abdomen. None had free gas under diaphragm. Retrocaecal shaft perforation was found in most of the cases. Post operative wound infection was found in 14.2% of the cases.Conclusions: Appendicular perforation is a severe complication of appendicitis. Appendicular perforation has no sex preference. It is common in elderly age group. Spread of pain from right iliacfossa to all over the abdomen, anorexia and rebound tenderness were found in all cases. Elevated total leukocytes count and shift to left were significant in case of appendicular perforation. Retrocaecal appendix is more prone to perforation.